SISTEM MANAJEMEN REKAM MEDIS DI PUSKESMAS TERAKREDITASI MADYA DAN TERAKREDITASI DASAR LOMBOK BARAT - Syamsuriansyah; Helmina Andriani; Rizal Adi Pratama; Uswatun Hasanah (Faculty of Medicine Universitas Mataram, 2022)
A medical record is a file that contains records and documents regarding patient identity, examination, treatment, actions, and services that have been provided to patients. Medical records are one of the assessments in the accreditation of PHC which are contained in Chapter VIII of standard 8.4 medical record information. The method used in this research is qualitative with in-depth interviews with 6 informants and each PHC namely puskesmas Narmada with middle accreditation and Puskesmas Karang Pule with basic accreditation and consists of 3 people, the person in charge of medical records and doctors. Checking the validity of the data using the triangulation method. The results of the study based on interviews, obtained standardization of diagnostic classification codes and standardization of abbreviations in both PHC using ICD-10 but in practice, Puskesmas Karang Pule was not in accordance with the SOP. Access to medical record information in both PHC is in accordance with the SOP. which was 5 years, while the medical records of Puskesmas Karang Pule that were still active and inactive were still stored on the same shelf. The conclusion of this study is that both PHC is good in the medical record management system but must be adjusted to the existing SOPs. Suggestions should be an evaluation in each health center related to the medical record management system.